Pedagogic competencies of special education teachers in develop vocational skills for students with intellectual disabilities - N. Dede Khoeriah; Nani Nur'aeni; Eka Yuli Astuti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This study aims to describe the pedagogical competence of teachers in vocational skills for students with intellectual disabilities. Vocational skills teachers at Special Education Schools are required to master the types and characteristics of students with special needs and the basics principles of special education. The research subjects were 37 special schools teachers in West Java Province. The research used a quantitative approach with the type of survey method and used as an evaluative method. This research is intended as validation to measure the effectiveness of the life skills training program model in developing social independence and productive work skills students with mild intellectual disabilities. The research technique used a questionnaire instrument with percentage data processing. The result showed : a) pedagogical competence in planning, qualitatively declare good (88,5 %); b) the understanding of educators to believe the importance of identifying individual programs (90%); c) educators conditioning the initial learning activities well (90%); d) the understanding of educators in competence to carrying out skills education well (90,5%), including: mastery material component development of systematic training strategies; e)reflection of educators by involving participants (87%), follow up by paying attention to completion of the participant’s assignments and by giving directions for enrichment activities or tasks (89%).